Human Development and the Transformation of the Academy - Richards, H (2011)
The idea of human is glossed in terms of agency and in terms of humans as the animals whose ecological niche is culture. The concept of "humanization by enlargement" is used to promote bringing modernity s other (non-modern cultures) into the curriculum. The objective is not only to celebrate what humans have been, are, and can be, but also to solve the intractable problems of modernity by mobilizing non-modern cultural resources. It is claimed that many indigenous peoples know things many modern peoples do not know about how to achieve social cohesion and how to live in a sustainable relationship to the natural environment. "Modernity" is glossed in terms of typical characteristics of successor states of the Roman Empire (Britain, France, etc.) which formed the European World-system that later expanded to become the Modern World-system. The ancient word "metaphysics" is put to use to promote mutual respect among cultures who read the world through different categories. © 2011 SAGE Publications.